Identification and Prioritization of Dimensions and Components Influencing Effective Entrepreneurship Education in Lower Secondary Schools - Etemadi, Fakhreddin (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to identify and prioritize the dimensions and components that influence effective entrepreneurship education in lower secondary schools in Iran.Methods and Materials: Using a mixed-methods approach (qualitative–quantitative), the study employed content analysis and a hybrid AHP-TOPSIS method to rank key influencing factors. Data were collected through semi-structured interviews with 13 experts (10 academic scholars and 3 executive specialists) and analyzed using thematic coding. This process resulted in the extraction of 136 subcomponents and 60 concepts across eight major dimensions.Findings: The findings revealed that socio-cultural factors (weight: 0.24)—especially societal attitudes toward entrepreneurship, the role of the family, and gender norms—had the greatest influence. Following this, factors related to the educational system (weight: 0.19), such as the inflexibility of the curriculum and deficiencies in teacher training, ranked second. Psychological-developmental dimensions (0.15), including self-efficacy and intrinsic motivation, and economic challenges (e.g., resource inequality), also showed a significant impact on outcomes. In contrast, environmental factors (0.04) received the least attention, indicating a gap between policy formulation and practical implementation.Conclusion: The study emphasizes the need to revise the curriculum by integrating digital tools, context-based content, and teacher empowerment programs to bridge the theory-practice divide. It also recommends the equitable allocation of resources and the design of entrepreneurship frameworks that are both culturally appropriate and aligned with global standards, while considering Iran’s socio-economic constraints. This research offers actionable insights for policymakers and educators to foster a generation of innovative and resilient entrepreneurs through context-sensitive educational strategies.